SoundArt 95 : Internationale Klangkunst Hannover. (Hannover : Sound Art e.V., 1995)
Anderson, Laurie ; Audio Ballerinas ; Auinger, Sam ; Quartett, Auryn ; Bosshard, Andres ; Demers, Louis-Philippe ; Eller, Ulrich ; Fahndrich, Walter ; Achim Freyer Ensemble ; Gierschik, Hans ; Jacobsen, Robert ; Julius, Rolf ; Kagel, Mauricio ; Kiefer, Peter ; Kubisch, Christina ; Kuhn, Hans Peter ; Leitner, Bernhard ; Leka, Dhora ; Minton, Phil ; Morgenstern, Jürgen ; Moss, David ; Odland, Bruce ; Panhuysen, Paul ; Rehmer, Jürgen ; Rose, Jon ; Rokeby, David ; Rutman, Bob ; Schafer, R. Murray ; Trayle, Mark ; Ulrichs, Timm ; Vorn, bill ; Wallis, Ulrike ; White, Red
SoundArt 95 : Internationale Klangkunst Hannover, 29. Mai - 30. Juni 1995
boek